PARTISIPASI MASYARAKAT KOTA PADANG DALAM PEMILU PADA TANGGAL 17 APRIL 2019 - Nazirwan Nazirwan; Ernita Ernita (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2019)
This study raises the issue of community participation in the city of Padang in the general election on April 17, 2019. Found in the field there are still many people who do not exercise their voting rights or abstentions, it is because many people work daily. Another problem that occurred in the city of Padang was a number of polling stations that did re-voting, amounting to 46 polling stations. The formulation of the problem in this study is How is the participation of the people of Padang in the elections on 17 April 2019, this research aims to obtain data and analyze and discuss how the Participation of the People of Padang in the Election on 17 April 2019. The population in this study were members of the Padang City Election Commission (KPU), Padang City Election Supervisory Board (PPL), and Padang City Communities. The sampling technique uses purposive sampling. The research data was collected from data sources and then, data collection can be done in various settings, various sources, and various ways. Based on the results of the study it can be seen that the Participation of Padang City People in the Election on April 17, 2019 was in the Good category with a percentage of 79.60%. For this reason it is expected that the General Election Commission (KPU) of Padang City will pay more attention and is expected to provide support, both in providing counseling on the importance of the people's suffrage for the progress of the Indonesian state by participating in general elections in the future.